2017
DOI: 10.1186/s12906-017-1632-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and cognitive-enhancing effects of the combined extract of Cyperus rotundus and Zingiber officinale

Abstract: BackgroundCurrently, food supplements to improve age-related dementia are required. Therefore, we aimed to determine the effect of the combined extract of Cyperus rotundus and Zingiber officinale (CP1) on the improvement of age-related dementia in rats with AF64A-induced memory deficits.MethodsMale Wistar rats weighing 180-200 g were orally given CP1 at doses of 100, 200 and 300 mg.kg-1 BW for a period of 14 days after bilateral intracerebroventricular administration of AF64A. Spatial memory was assessed in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 41 publications
(27 reference statements)
0
31
0
Order By: Relevance
“…a-Cyperone, extracted from Cyperus rotundus, has been demonstrated to weaken the inflammatory response by microtubule destabilization in the brain (Azimi et al, 2016). Sutalangka et al has reported Cyperus rotundus has neuroprotective and cognitive-enhancing effects in AF64A-treated rats (Sutalangka and Wattanathorn, 2017). We previously showed that a-cyperone exerts neuroprotective effects by inhibiting microglia-mediated neuroinflammation (Huang et al, 2018).…”
Section: Introductionmentioning
confidence: 87%
“…a-Cyperone, extracted from Cyperus rotundus, has been demonstrated to weaken the inflammatory response by microtubule destabilization in the brain (Azimi et al, 2016). Sutalangka et al has reported Cyperus rotundus has neuroprotective and cognitive-enhancing effects in AF64A-treated rats (Sutalangka and Wattanathorn, 2017). We previously showed that a-cyperone exerts neuroprotective effects by inhibiting microglia-mediated neuroinflammation (Huang et al, 2018).…”
Section: Introductionmentioning
confidence: 87%
“…The results of the in vitro AChE inhibition studies performed by other authors have been confirmed by several in vivo assays, that determine the actual activity of ginger extracts or fractions in living organisms. Sutalangka and Wattanathorn [1] observed in their study on rats that after an oral administration of Zingiber officinale and Cyperus rotundus extracts the cognition and memorizing processes were elevated and AChE activity decreased. These extracts were found to affect the cholinergic functions of brain and decrease neurodegeneration and oxidative stress.…”
Section: Introductionmentioning
confidence: 97%
“…The currently available medications can slow down the progression of dementia, but not to treat it. Based on the above information, the search for new potential drug candidates that retard the progression of memory impairment is of the highest importance [1,2]. Among the mechanisms of dementia are disturbances in acetylcholine synthesis and an overproduction of esterases, that decompose this neuromodulator, have been highlighted in various scientific reports.…”
Section: Introductionmentioning
confidence: 99%
“…In experimental hypothyroidism, thyroid hormones dysfunction has been reported to directly relate to ACh deficiency in particular parts of the brain including hippocampus and basal forebrain (Patel, Hayashi, & Hunt, 1987;Patel, Smith, Kingsbury, Hunt, & Balazs, 1980;Smith et al, 2002). On the contrary, all herbs used in the current study, including C. sativus (Geromichalos et al, 2012), C. rotundus (Sutalangka & Wattanathorn, 2017), B. serrate (Yassin et al, 2013), and P. nigrum (Ingkaninan, Temkitthawon, Chuenchom, Yuyaem, & Thongnoi, 2003) have been reported to increase ACh content in the brain through reducing the AChE activity.…”
Section: Central Cholinergic Transmission Deficiency Is An Importantmentioning
confidence: 56%
“…rotundus is a potent antioxidant and acetylcholinesterase (AChE) inhibitor, which is reported to exert neuroprotective and memory-enhancing effects (Mehdizadeh et al, 2017;Sutalangka & Wattanathorn, 2017). C. sativus (saffron) traditionally used as a food additive and a medical plant (Akhondzadeh et al, 2010;Pitsikas et al, 2007).…”
Section: Introductionmentioning
confidence: 99%